Blockchain technology: uninvestigated issues emerging from an integrated view within accounting and auditing practices. Issue 2 (29th January 2021) - Maffei, Marco; Casciello, Raffaela; Meucci, Fiorenza
Abstract : Purpose: The aim of this paper is to explore the effects of adopting and implementing blockchain technology (BT) in accounting and auditing practices in terms of benefits and threats, thus discovering new and upcoming risks and issues. Design/methodology/approach: This paper adopts a critical perspective to investigate how the implementation of BT could affect accounting and auditing practices, providing a reflection on the role of accountants and auditors during such a technological revolution. Findings: This paper highlights the importance of the unreplaceable professional conscience and experience of accountants and auditors compared to the impersonal and standardised operating system of artificial intelligence provided by BT. The development and diffusion of BT are leading professionals to acquaint themselves with new accounting and auditing systems, such as reinventing old practices and finding new ways of taking advantage of blockchain instead of being overwhelmed. Originality/value: Different from the majority of previous literature contributions, this study looks beyond the potential and undeniable benefits that BT can offer to accounting and auditing environments by focussing especially on the threats and risks caused by its implementation.